Rancang Bangun Aplikasi Kasir Penjualan pada Usaha Mikro Kecil Mengengah 3Manstore Berbasis Web - Asri Mulyani; Ridwan Setiawan; Ruli Ahmad Rusmana (Institut Teknologi Garut, 2022)
The sales cashier application for micro, small and medium businesses is the answer to the problems that exist in one of the micro, small and medium businesses making bags in the Leles area, Garut Regency. The results of observations and interviews with micro, small and medium business owners, the problems that exist are that the transaction process is still manual using written notes, so it is very risky for notes to be lost or damaged, the profit calculation process is sometimes out of balance due to human error during the recapitulation process and there is no debt record so that when the reseller debt payment process is sometimes out of sync. The purpose of making this application is to help process sales activities in micro, small and medium enterprises, help manage accounts payable, and assist in the process of recapitulating income statements. Rational Unified Process (RUP) in which the implementation stages only include inception, elaboration, and construction is part of the methodology used. Then using Uinifbieid Miodeilling Language modeling and alpha testing using the Black Box Ties method is carried out at the construction stage, while programming languages PHP and MySQL are the databases. The results of this research are in the form of a Sales Cashier Application for Web-Based Micro, Small, and Medium Enterprises that chooses multi-user access rights and is equipped with transaction features, debt management, and income statements.